Efek Mobilisasi Upper Thoracal LPAVP pada Rom Bidang Sagital Kasus Spondyloarthrosis Cervicalis (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2009)
This research aims to detect mobilization increasing influence upper thoracal lpavp in mwd and traction statik manual position fleksi towards enhanced rom area sagital in spondyloarthrosis cervicalis. Watchfulness is done at physiotherapy clinic rs pelni and RSAL Mintohardjo Jakarta go on since June to August 2008. Sample numbers 20 person, sample taking is done technique purposive sampling, divided to be 2 groups. Treatment group is sample total 10 person are given mwd and traction static manual position fleksi. treatment group II sample total 10 person given mwd, traksi static manual po-sition fleksi and mobilization upper thoracal lpavp. Result and effect that got from control group intervention and treatment enhanced rom. As to test result t-test related in control group with standard signifikan=0,000,p<0,05 mean ho aversed so that there influence very significant intervention gift mwd and traksi statik manual position fleksi towards enhanced rom area sagital.Â  Test t-test related treatment group with standard sigini-ficant=0,000,p<0,05 mean ho aversed so that there influence very significant intervention gift mwd, traksi static manual position fleksi and mobilization upper thoracal lpavp towards enhanced rom area sagital. While in test t-test independent got standard result siginifikan=0,108,p>0,05 so that ho fail to aversed, that mean there is no difference significant between control group with treatment group.Keywords: LPAVP, Traction Static Manual Position Fleksi, Spondyloarthrosis Cervicalis